The Professional Dilemma â€“ To Wield the Stick for Once or to Yield Yet Again : A Case Analysis - Datta, Sugata; Bindu Madhavi, N. (Prabandhan: Indian Journal of Management, 2018)
This case study discussed how multiple unions in one organization can lead to conflict of interest and make things difficult for the Management. Handling indiscipline and industrial relations is not only about rules and statutes, but requires the ability of HR and IR professionals to be able to foresee and strategize each and every action. To be able to get the desired outcome, it is necessary to have a basket of effective strategies. A workable Plan â€œA," Plan â€œB,â€ and preferably Plan â€œCâ€ should be in place. However, the sequence of rolling out either or all of the plans need not be in the alphabetical order. It needs to be situational. When it comes to man management, being tough is a professional requirement, but managing people from the heart with the aim of achieving a win-win situation is probably the best policy.